1999
DOI: 10.1046/j.1365-2249.1999.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection of human endothelial cells withStaphylococcus aureusinduces the production of monocyte chemotactic protein-1 (MCP-1) and monocyte chemotaxis

Abstract: Bacterial infection coincides with migration of leucocytes from the circulation into the bacterium-infected tissue. Recently, we have shown that endothelial cells, upon binding and ingestion of Staphylococcus aureus, exhibit proinflammatory properties including procoagulant activity and increased intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) expression on the cell surface, resulting in hyperadhesiveness, mainly for monocytes. The enhanced extravasation of monocytes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
44
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 35 publications
9
44
0
Order By: Relevance
“…We previously reported that S. aureus upon internalization by EC induces monocyte adhesion and chemotaxis by increasing EC surface expression of ICAM-1 and VCAM-1 molecules (9) and secretion of MCP-1 (40). In extension to this, the present study shows a similar response of EC after infection with S. epidermidis or S. sanguis.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…We previously reported that S. aureus upon internalization by EC induces monocyte adhesion and chemotaxis by increasing EC surface expression of ICAM-1 and VCAM-1 molecules (9) and secretion of MCP-1 (40). In extension to this, the present study shows a similar response of EC after infection with S. epidermidis or S. sanguis.…”
Section: Discussionsupporting
confidence: 85%
“…Our previous studies demonstrated that virulent as well as less virulent S. aureus organisms and to a lesser extent S. sanguis and S. epidermidis infect and colonize EC in culture (9,40,43). As a result of infection with S. aureus, but not S. sanguis or S. epidermidis, EC are activated to express TF mRNA, TF surface antigen, and TFA (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of those genes that were differentially regulated, ICAM-1 and MCP-1 are interesting candidates for further study, as these molecules may act as part of an inflammatory host response to infection (71)(72)(73). ICAM-1 is an inducible cell adhesion glycoprotein of the Ig supergene family expressed on the surface of a wide variety of cell types (74), and may be up-regulated in response to proinflammatory cytokines, hormones, cellular stresses, and virus infection to promote intercellular signaling during inflammation (75).…”
Section: Discussionmentioning
confidence: 99%